Human posture recognition classifiers - Htike, Kyaw Kyaw; Khalifa, Othman Omran; Lai, Weng Kin; Islam, Md. Rafiqul (IIUM Press, 2011)
Human activities recognition is becoming a field of great interest and relevance to a number of areas of research and applications The availability of a system capable of automatIcally classifying the physical activity performed by a human subject is extremely attractive for many applications such as in surveillance and security systems, choreography, sports, virtual reality, human-computer interaction, content-based image and video retrieval, automanc scene understanding and other vision-based interfaces. In particular, there has been incredible growth in the volume of computer vision research geared at understanding human actions and behaviors. These advances range from classification of basic low-level activities such as recognizing someone walking or sitting, to the higher level task of recognizing an interpreting the global behavior of several interacting people